Smooth Car Rental Sdn. Bhd - John, Jennifer; Marandan, Finoh; Rapael, Rosalind; Ahmadi, Mohammad Adzim Idzaim; Moktin, Adiasnawi (2016)
Smooth Car Rental is a business that operate car rental services . Our business located at Taman Indah Permai, Kota Kinabalu Industrial Park. While there are many Car Rental services our services excel due to its attention to detail regarding our users. Moreover, we are believed that we will successfully compete with our competitors in a few years ahead. This is because nowadays client will choose the best services to use. Customer will choose the company who give them the best services in term of quality and prices.